Evaluation of the modified braille dots printed with the UV ink-jet technique - Urbas, Raša; Rotar, Bojan; Hajdu, Peter; Stankovič Elesini, Urška (Journal of Graphic Engineering and Design, 2016)
Braille presents a complex system of writing with additional symbols and letters designating numbers, capital letters and other special symbols in mathematics, physics, music etc. Due to mentioned braille texts are usually very long, bulky, space consuming and complex. In this research a study of modified braille dots is presented. Samples were prepared in several different steps, enabling the determination of the optimal braille dot height on top which additional elements were printed. Properties of ordinary braille dot samples and braille dot samples printed with additional element were compared and analyzed. An extensive sensory analysis with blind and visually impaired people was performed for establishing weather modified braille dots can be tactile recognized and used in practice.